Answer:
Part 1) [tex]y=3(x+\frac{4}{3})^{2}-\frac{10}{3}[/tex]
Part 2) [tex]y=-2(x-\frac{3}{2})^{2}+\frac{5}{2}[/tex]
Step-by-step explanation:
Part 1) we have
[tex]y=3x^{2}+8x+2[/tex]
Factor the leading coefficient 3
[tex]y=3(x^{2}+\frac{8}{3}x)+2[/tex]
Complete the square
[tex]y=3(x^{2}+\frac{8}{3}x+\frac{64}{36})+2-\frac{64}{12}[/tex]
[tex]y=3(x^{2}+\frac{8}{3}x+\frac{64}{36})-\frac{40}{12}[/tex]
Rewrite as perfect squares
[tex]y=3(x+\frac{8}{6})^{2}-\frac{40}{12}[/tex]
simplify
[tex]y=3(x+\frac{4}{3})^{2}-\frac{10}{3}[/tex]
The vertex is the point [tex](-\frac{4}{3},-\frac{10}{3})[/tex]
Part 2) we have
[tex]y=-2x^{2}+6x-2[/tex]
Factor the leading coefficient -2
[tex]y=-2(x^{2}-3x)-2[/tex]
Complete the square
[tex]y=-2(x^{2}-3x+\frac{9}{4})-2+\frac{9}{2}[/tex]
[tex]y=-2(x^{2}-3x+\frac{9}{4})+\frac{5}{2}[/tex]
Rewrite as perfect squares
[tex]y=-2(x-\frac{3}{2})^{2}+\frac{5}{2}[/tex]
The vertex is the point [tex](\frac{3}{2},\frac{5}{2})[/tex]